ECONOMIC STANDARD – QUANTITATIVE COMPONENT OF QUALITY OF LIFE - ROXANA PLEŞA (Annals of the University of Petrosani: Economics)
In the present social/economic conditions of our country, the problem of objective analysis and research of the population’s everyday social life, of its wellbeing, of final consumption and possibilities of satisfying vital necessities, of the living standard and lifestyle, of the quality of life as a whole, becomes more and more present and significant. In the present period, the concept of quality of life was not only used by specialist, it actually became “exchange currency” in public debates. Considering the political and economic context and the integration of Romania in the European Union, the assurance of life quality is a vital objective in order to rapidly reach a living standard at acceptable level of civilization, defined in a European context.